Impact of Prior Virological Failure and Nucleos(t)ide Genotypic Resistance Mutations on the Efficacy of Switching from Ritonavir-Boosted Protease Inhibitors to Raltegravir. Issue 5 (July 2015) - Blanco, José L; Gonzalez-Cordón, Ana; Llibre, Josep M; Calvo, Marta; Gutierrez, Felix; Podzamczer, Daniel; Laguno, Montserrat; Fumero, Emilio; Murillas, Javier; Mallolas, Josep; Martinez-Rebollar, Maria; Lonca, Montserrat; et al.
Background: The virological efficacy of switching from a ritonavir-boosted protease inhibitor (PI/r)- to a raltegravir (RAL)-containing regimen remains controversial according to the results of SWITCHMRK and SPIRAL studies. The aim of this analysis is to assess the impact of prior resistance mutations to nucleos(t)ides and other potential factors on the virological outcome. Methods: This was a substudy of the prospective, open-label, multicentre SPIRAL study. Demographic, virological variables, prior episodes of virological failures (VF) and archived resistance mutations to nucleos(t)ides were identified from databases and its impact measured by genotypic sensitive scores (GSS) according to the genotypic resistance interpretation algorithm from the Stanford HIV Drug Resistance Database on outcome was analysed. Results: Of 250 patients (128 RAL and 122 PI/r) included in the main SPIRAL study, 74 (30%) had previous VF with prior genotypic resistance tests (GRT). Median time of virological suppression prior to inclusion in SPIRAL study was 63.5 months. GSS for backbone nucleos(t)ides was <1 in 15/38 (39%) in the RAL arm and in 9/36 (25%) in the PI/r arm ( P =0.13). Among those with nucleos(t)ides GSS <1, 0/15 (0%) in the RAL versus 2/9 (22%) in the PI/r arm developed VF ( P =0.13). Moreover 0/11 subjects with null or residual (GSS≤0.5) backbone activity developed VF in the RAL arm. Conclusions: The 48-week virological efficacy of switching from a PI/r to RAL in subjects with long-term virological suppression was not compromised by a reduction of the nucleos(t)ide backbone activity.